2019
DOI: 10.3390/nu12010081
|View full text |Cite
|
Sign up to set email alerts
|

Actions Targeting the Double Burden of Malnutrition: A Scoping Review

Abstract: Background: In many developing countries, nutritional and epidemiological transitions are contributing to continuous undernutrition and escalating overnutrition, resulting in coexisting forms of malnutrition often referred as the “double burden of malnutrition” (DBM). This complex phenomenon constitutes an unprecedented challenge to global public health and has been prioritized by international health organizations, prompting governments to swift action. Specifically, five years ago the World Health Organizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 20 publications
(33 reference statements)
1
20
0
2
Order By: Relevance
“…These findings indicate the existence of the two forms of malnutrition (under nutrition and over nutrition) in Tanzanian primary school children and highlight the importance of considering both forms of malnutrition in future studies. The prevalence of thinness and overweight/obesity observed, were similar to what has been reported recently in a scoping review [26].…”
Section: Plos Onesupporting
confidence: 89%
“…These findings indicate the existence of the two forms of malnutrition (under nutrition and over nutrition) in Tanzanian primary school children and highlight the importance of considering both forms of malnutrition in future studies. The prevalence of thinness and overweight/obesity observed, were similar to what has been reported recently in a scoping review [26].…”
Section: Plos Onesupporting
confidence: 89%
“…There are country-specific thresholds signifying the number of years of schooling needed for a significant reduction in child malnutrition [66]; accordingly, Ethiopia also needs to develop a contextual threshold level because primary education alone may not be enough to make the needed nutritional impact. Behavioral interventions and health promotion initiatives tailored to the mother's level of understanding could be one opportunity, however, there is limited evidence on its implementation and success in tackling under-and over-nutrition simultaneously [67].…”
Section: Discussionmentioning
confidence: 99%
“…However, five years after the failed attempt to relaunch the FNS, not only is it necessary to deal with the food access by the most vulnerable due to the latest economic declines [1] but also to deal with excess consumption, the so-called "double burden of malnutrition", where undernutrition and obesity co-exist [6,23]. The "double burden" brings serious macro effects on health [36,60,63], the economy [24,86], and the environment [87][88][89]. Therefore, beside the measures existing in the FNS, it is also important to tackle other contextual inequalities shown that this study has shown has a direct influence on food security, including gender disparities, income inequality, education, and regional differences.…”
Section: Discussionmentioning
confidence: 99%